Maintaining Health from an Early Age: Building PHBS Awareness among PMI Children in Malaysia - Roisah Roisah; Amalia Fauziah Zahra; Joanna Valencia; Atika Putri Chairani; Avrielle Mauliaraudhah Farmudya; Azzahra Arimbi Kamila; Della Monica; Fong Handoko; Sri Devi Aryanti; Livia Ramadhani; Siti Nur Azizah (Universitas Muhammadiyah Purwokerto, 2024)
Health is significant for every individual, especially for growing and developing children growing and developing children. However, children of Indonesian migrant workers (PMI) living in Malaysia often face challenges in maintaining their health. Factors such as the environment, access to health services, and awareness of good health practices usually become barriers. Therefore, the International Volunteering Chapter Malaysia held by Youth Indonesia on 20-25 February 2024 at Sanggar Bimbingan Malaysia is an effort to help build awareness about Clean and Healthy Living Behavior (PHBS) among PMI children in Malaysia. Various work programs have been implemented during this activity period to increase PHBS awareness among PMI children. These programs include various activities, ranging from counseling about PHBS, correct hand washing practices, and maintaining environmental cleanliness to healthy eating patterns. Through collaboration between Youth Indonesia volunteers, Sekolah Indonesia Kuala Lumpur (SIKL), and the Embassy of the Republic of Indonesia (KBRI) Kuala Lumpur, these programs have succeeded in creating a supportive environment for building PHBS awareness among PMI children. Evaluations carried out on the impact of these programs show significant improvements in the knowledge, attitudes and behavior of PMI children related to health and PHBS. The participants showed high interest in continuing to learn and apply the health practices they learned during this activity. It shows that the International Volunteering Chapter Malaysia has positively contributed to building PHBS awareness among PMI children in Malaysia. Thus, this activity is not just an activity but is also part of a real effort to create positive changes in the lives of PMI children in Malaysia.